Influence of the TGT Cooperative Learning Model on Students’ Social Science Academic Performance - Nurul Fahira; Sri Buwono; Venny Karolina; Hadi Wiyono; Thomy Sastra Atmaja (Edumaspul: Jurnal Pendidikan, 2023)
This research was conducted to determine the influence of the Teams Games Tournament (TGT) learning model on the learning outcomes of seventh-grade students in the subject of Social Science. This study used a quantitative approach with a quasi-experimental design method, involving both a control group (lecture-based teaching model) and an experimental group (TGT cooperative learning model). The research yielded results indicating that there was no significant influence of the conventional learning model on learning outcomes, as evidenced by the asymptotic significance (2-tailed) value of 0.053 which means that is higher than 0.05. Furthermore, the study demonstrated a significant influence of the TGT learning model with an asymptotic significance (2-tailed) value of 0.000 which is lower than 0.05. The research findings indicate that the TGT model has a significantly greater impact on students’ social science learning outcomes compared to the conventional learning model, with an effect size of 0.368, which falls into the medium category